Implementasi Model Kooperatif TGT dalam Pembelajaran PAI di Era Digital untuk Mendorong Keaktifan Siswa Kelas 8 SMPN 2 Waru - Melani Agustiyaningsih; Abd Muqit; Junaedi Junaedi (Prodi Pendidikan Keagamaan Islam, 2026)
Islamic Religious Education (IRE) learning in the digital era often faces the challenge of student passivity, especially in junior high schools, thus requiring innovation to increase student activity. This study aims to describe the implementation of the Teams Games Tournament (TGT) cooperative model integrated with digital media to encourage the activity of 8th grade students at SMPN 2 Waru in the even semester of 2024/2025. The study employs a qualitative descriptive approach with a field study design, involving IRE students and teachers as key informants. Data were collected through observation, interviews, and documentation. The results showed an increase in student active participation in discussions, digital-based games, and tournaments, a decrease in passive behavior, and an increase in collaboration. This study concluded that the TGT model in the digital era encourages student activity in PAI learning.